- PENGGUNAAN PASAL 351 AYAT (1) KUHP TERHADAP PERBUATAN PENGANIAYAAN MENGAKIBATKAN LUKA BERAT DI KEPAHIANG, BENGKULU: - - Candra Aries Priyendi; Setiyono (Faculty of Law, Universitas Trisakti, 2023)
At the Kepahiang District Court with Decision Number 46/Pid.B/2022/PN Kph, the trial for the criminal act of persecution resulted in serious injury. In the trial process, there was an inaccuracy in the application of the article. So the formulation of the problem in this research is whether the act of persecution which resulted in serious injury committed by the defendant is in accordance with Article 351 (1) of the Criminal Code (KUHP) against and whether the criminal sanction given by the panel of judges in Decision No. 46/Pid.B/2022/PN Kph is in accordance with the purpose of sentencing. The research is a normative legal manner, descriptive, use secondary data. Then then the data processing used is qualitative and drawing conclusions using deductive logic. The results of this research, discussion and conclusion are of course that in essence the act of persecution was an act of error, in which this act violated the norms of law and norms of society, so that the use of Article 351 (1) of the KUHP for acts of persecution which resulted in serious injuries committed by Agustian was not in accordance . Law enforcement officials must also be more careful in terms of imposing penalties.